Thirty-Eighth Meeting of the National Development Council 8th and 9th November 1985 Summary Record - Planning Commission (Planning Commission, 1985)
The National Development Council commenced its deliberations with Dr. Manmohan Singh, Deputy Chairman, Planning Commission making a reference to the void left by the absence of Shrimati Indira Gandhi. He recalled that Shrimati Gandhi had presided over the deliberations of the Council for nearly sixteen years. She had a profound impact on the evolution of India's economy and polity with her strong commitment to the goals of modernisation, development, social justice and self-reliance. These had inspired several new thrusts in our development plans and programmes. The achievement of self-sufficiency in foodgrains and the inculcation of scientific temper in Indian agriculture, a vast increase in the nation's technical and managerial reservoir, a diversified industrial structure and the inclusion in the Plans of several innovative programmes aimed specially at the weaker sections among whom could be enumerated, particularly, agricultural labourers, small and marginal farmers, scheduled castes and scheduled tribes, were all a tribute to Shrimati Gandhi's vision and indomitable courage as the nation's leader.
Government of India Planning Commission
Government of India Planning Commission